A multiplex PCR detection method for milk based on novel primers specific for Listeria monocytogenes 1/2a serotype. (April 2018) - Sheng, Jie; Tao, Tingting; Zhu, Xiaoyu; Bie, Xiaomei; Lv, Fengxia; Zhao, Haizhen; Lu, Zhaoxin
Abstract: Listeria monocytogenes serotype 1/2a is considered as a foodborne pathogen, resulting in high morbidity. Detection of Listeria monocytogenes serotype 1/2a is rather difficult and time-consuming thus, the need for better detection methods is encouraged. In order to rapidly detect and identify L. monocytogenes serotype 1/2a, specific target genes were mined by the comparative genomics approach. Three specific primers based on novel specific targets were screened. The primers were m2a1, m2a4, and m2a8. The m2a4 primer was the most sensitive and stable among the three. A multiplex PCR method for detecting 1/2a serotype was developed by combining the serotype-specific primer m2a4 and species-specific primer Lm8 of gene LMOf2365_2721. The detection limit of the multiplex PCR was 305.5 fg/μL for genomic DNA and 8.6 × 10 3  cfu/mL for L. monocytogenes serotype 1/2a, respectively. And the primers for the detection of L. monocytogenes serotype 1/2a was not interfered by genome DNA of other L. monocytogenes serotypes 1/2b, 1/2c, 3a, 4b in different concentrations. The artificially contaminated milk with L. monocytogenes serotype 1/2a of 8.6 × 10 4 –8.6 × 10 0  cfu/10 mL could be detected successfully with the multiplex PCR method after 6–12 h of enrichment. These results suggested that the multiplex PCR assay was able to rapidly detect and identify L. monocytogenes serotype 1/2a and exhibited high specificity and sensitivity. Therefore, the detection process of the serotype 1/2a in food could be accomplished at less than 8.6 × 10 4  cfu/10 mL of contamination in 9–15 h. Highlights: A pair of novel primers m2a4 specific for L. monocytogenes serotype 1/2a was designed. A multiplex PCR method was developed, combining m2a4 with species-specific primers Lm8. The method appeared to be specific, sensitive, reliable, and had a run-time of 9–15 h. It could be applied to the rapid screening of L. monocytogenes serotype 1/2a in food.